2021
DOI: 10.26656/fr.2017.5(s1).030
|View full text |Cite
|
Sign up to set email alerts
|

Flower bagging effects on the α-mangostin content during mangosteen fruit growth

Abstract: Mangosteen fruit (Garcinia mangostana L.) is consumed mainly for two purposes, i.e., its aril for fresh or minimally processed products and its rind for herb and other health-related products. In fact, due to the high portion of rind compared to its whole fruit, its rind has a more important economic value, especially for its α-mangostin content. This study reported the effects of flower baggings on the α-mangostin content during mangosteen fruit growth. This field research was conducted in a farmer’s field at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, Akmal et al (2023) reported that mangosteen fruit, located either outside or inside the canopy, that were enclosed with either transparent or black plastic bags showed no differences in fruit color development. The α-mangostin content in the pericarp increased markedly during the 10-to 14-week period after anthesis, and that increase was not affected by bagging, bagging materials, or application periods (Widodo et al, 2021). In each of the experiments mentioned above, the bagging treatments were limited, and bagging removal was not investigated to determine if subsequent light exposure affected anthocyanin accumulation and the expression of genes in the anthocyanin biosynthetic pathway.…”
Section: The Impacts Of Light On Anthocyanin Contentmentioning
confidence: 99%
“…Similarly, Akmal et al (2023) reported that mangosteen fruit, located either outside or inside the canopy, that were enclosed with either transparent or black plastic bags showed no differences in fruit color development. The α-mangostin content in the pericarp increased markedly during the 10-to 14-week period after anthesis, and that increase was not affected by bagging, bagging materials, or application periods (Widodo et al, 2021). In each of the experiments mentioned above, the bagging treatments were limited, and bagging removal was not investigated to determine if subsequent light exposure affected anthocyanin accumulation and the expression of genes in the anthocyanin biosynthetic pathway.…”
Section: The Impacts Of Light On Anthocyanin Contentmentioning
confidence: 99%